Penggunaan Antikejang Pada Cedera Kepala: Tinjauan Sistematis - Nabila Zafira, Safa; Aulya Kemuning, Diva; Izzatush Sholihah, Nur; Nooradi Praramdana, Muhammad (CV RIFAINSTITUT, 2022)
Brain injury can occur due to direct head impact and injury due to brain tissue damage such as hypotension, hypoxia, acidosis and edema. Brain injury will trigger an inflammatory process that can lead to post-trauma seizures. The use of anti- epileptic drugs is intended as a seizure prophylaxis so that it can reduce the incidence of seizures in the early phase of injury. Quantify the effectivity of anti seizure usage on post traumatic seizure accident. The method used in this paper is a relevant systematic review from various references and focuses on the use of analgesics for the management of seizures due to brain injury. The literature search used PubMed and found 7 literature that met the criteria. Consists of 1 RCT study and 6 observational studies. Prophylactic therapy in the incidence of head injury is effective in preventing PTS. The use of anti seizure can be given to patients with moderate or severe TBI and can be given less than 12 hours after injury to prevent seizures. Prophylactic therapy is only recommended for 7 days after head injury. Anti seizure drug which is often used as a prophylactic agent are phenytoin and levetiracetam. Lacosamide is recommended for users with refractory status epilepticus. Levetiracetam has fewer side effects than phenytoin and lacosamide, so the use of this drug is preferable to use.Using Anti seizure in cases of post-traumatic brain injury (TBI) or post traumatic seizure (PTS) is behoof as a seizure prophylactic attempt by using recommendation less than eight days because OAE has been shown several side effects, include increasing mortality. Especially for using phenytoin and lacosamide, it is necessary to monitor